Psycholinguistics in Arabic Learning: History and Urgency - Tulus Musthofa; Zulfa Amalia Wahidah (Arabic Education Program IAIN Pekalongan, 2020)
This study is expected to minimize the stigma attached to the students’ minds about the complexity in the structure and grammar of Arabic, as well as the difficulty of finding the Arabic equivalent in Indonesian. These difficulties can be resolved through psycholinguistic understanding. This study tried to describe solutions to problems in learning Arabic as a second language based on a psycholinguistic perspective. This article offers three principles that guide successful language learning. They are principles of education, psychology, and linguistics. This study used a qualitative method with a library research. The main references included books, journals, articles, proceedings, and researches related to the role of psycholinguistics in Arabic learning. The results of psycholinguistic studies are widely used to understand students’ second-language learning in formal education. The scope of psycholinguistics has proven to be very beneficial for language learning.